Efficacy of Narrative Exposure Therapy and Age Differences on Psychological Trauma Symptoms among Internally Displaced Persons in Jos, Plateau State, Nigeria - Ishaya, Dashit Samson; Ibrahim, Teplong Joyce; Gana, John Gospel (NIU Journal of Social Sciences, 2020)
There are growing need for experiential literatures on psychological trauma symptoms and corresponding therapies, considering traumatic experience in Nigeria. The present study had assessed efficacy of narrative exposure therapy and age differences on psychological trauma symptoms among internally displaced persons. A repeated measures design was used to examine pre-test and post-test outcomes. The participants used for the study were 24 internally displaced persons (8 males and 16 females) who were randomly selected and assigned into two (psychological intervention and control) groups. Trauma Symptoms Checklist-40 (TSCL-40) was used in assessing all the participant and the treatment group had 10 sessions of NET therapy, while the control group was without intervention. The study hypothesis was statistically tested, using one-way analysis of variance. The outcome of the ANOVA for the hypothesis tested revealed, that Narrative Exposure Therapy (NET) was more impactful on younger participants than older ones on two symptoms; depression (F = 9.712, p = 0.011), and sexual problems (F = 6.665, p = 0.027). The hypothesis was therefore upheld for only depression and sexual problems. There is need for more psychological studies to be conducted amongst children at internally displaced camps so that both young and old would have gone through the therapy. Keywords : Psychological Trauma, Symptoms, Age differences, Narrative exposure therapy, Internally Displaced Persons.